Characteristics of lactic acid bacteria isolates and their effect on the fermentation quality of Napier grass silage at three high temperatures. (22nd September 2016) - Gulfam, Ali; Guo, Gang; Tajebe, Seare; Chen, Lei; Liu, Qinhua; Yuan, Xianjun; Bai, Yunfeng; Saho, Tao
Abstract: BACKGROUND: The poor fermentation quality of silage is an important issue for silage production during the high temperatures of summer. Pediococcus acidilactici GG13 (GG13) and Lactobacillus rhamnosus GG26 (GG26) isolated from Italian ryegrass ( Lolium multiflorum Lam.) silage were characterised by morphological and physiological tests and 16S rRNA sequencing analysis, and their effects, along with those of a commercial lactic acid bacteria (LAB) inoculant (CB), on the fermentation quality of facultative halophyte Napier grass ( Pennisetum purpureum Schumach) ensiled at 30 °C, 40 °C and 50 °C were studied, respectively. RESULT: The strains GG13 and GG26 grew well at 50 °C and pH 3.5, and were tolerant to 6.5% NaCl. After ensiling for 50 days, the strains GG13 and GG26 and the CB decreased ( P < 0.001) the pH and acetic acid and ammonia‐N contents and increased ( P < 0.001) the lactic acid contents at 30 °C, and decreased ( P < 0.001) the ammonia‐N contents at 40 °C in Napier grass. CB did not affect the fermentation quality at 50 °C, whereas both isolated strains improved the fermentation quality of Napier grass silage as indicated by the lower ( P < 0.001) pH, butyric acid and ammonia‐N contents and higher ( P < 0.001) lactic acid contents. The strain GG13 is better than GG26 with regard to improvement in fermentation quality of Napier grass silage. CONCLUSIONS: The results of this study suggested that strain GG13 is a good LAB inoculant for producing well‐fermented silages during the high temperatures of summer times. © 2016 Society of Chemical Industry